Androgen receptor serine 81 mediates Pin1 interaction and activity - La Montagna, Raffaele (Landes Bioscience, 2012)
Hormone-dependent tumors are characterized by deregulated activity of specific steroid receptors, allowing aberrant expression of many genes involved in cancer initiation, progression and metastasis. In prostate cancer, the androgen receptor (AR) protein has pivotal functions, and over the years it has been the target of different drugs. AR is a nuclear receptor whose activity is regulated by a phosphorylation mechanism controlled by hormone and growth factors. Following phosphorylation, AR interacts with many cofactors that closely control its function. Among such cofactors, Pin1 is a peptidyl-prolyl isomerase that is involved in the control of protein phosphorylation and has a prognostic value in prostate cancer. In the present study, we demonstrate that ARSer81 is involved in the interaction with Pin1, and that this interaction is important for the transcriptional activity of AR. Since Pin1 expression positively correlates with tumor grade, our results suggest that Pin1 can participate in this process by modulating AR function.